Non-standard dictionary definitions: What they cannot tell native speakers of Polish - Lew, Robert; Dziemianko, Anna (Cadernos de Traduçao, 2006)
Recently, a new defining format has been gaining in popularity in abstract noun entries of monolingual English learners’ dictionaries: a single-clause when-definition. The present study attempts to investigate the role of the definition of this format, placed in a complete microstructure, in conveying information on the syntactic class of nominal headwords. To achieve this aim, tests were designed and run on several groups of Polish learners of English at the intermediate level. Balanced parallel forms were employed, where single-clause when-definitions were contrasted with their closest analytical analogs in full dictionary entries. It was found that both the new and the classical definition formats resulted in comparably frequent correct POS identification of the headword nouns. This is in stark contrast to the results yielded by Lew & Dziemianko’s research (in press), which has inspired the present analysis, where the definition formats were investigated in isolation from other components of the microstructure. Analysis of the consultation behaviour suggests that the syntactic label was the only element of the entry consulted with any frequency, which suggests that the subjects may have approached the task as a metalexicographic exercise.
Keywords: Definition; Folk defining; Lexicography; Syntactic information; Syntax; Monolingual dictionary; Definition format; Learner's dictionary